2021
DOI: 10.3390/en14248346
|View full text |Cite
|
Sign up to set email alerts
|

Interior Heating and Its Influence on Electric Bus Consumption

Abstract: This paper focuses on the statistical evaluation of various operating characteristics of electric buses. The data obtained for statistical evaluation come from practice. In this paper, we focus on electricity consumption—an important aspect of electric bus operation. The ambient temperature significantly affects electricity consumption. In this paper, we use applied mathematics—correlation analysis, we accurately identify the effect of temperature on the consumption of the electric bus. Our next goal was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Eufrásio et al [26] conducted a study in São Paulo and reported an average consumption of 1.19-1.27 kWh/km, of which they found higher energy consumption on hotter days. Different studies provide statistical analyses on energy consumption in relation to temperature [27,28]. Culik et al [27] performed a statistical analysis on 14,888 trips and found that lower temperatures increased energy consumption.…”
Section: Data Analysis In Beb Operationsmentioning
confidence: 99%
“…Eufrásio et al [26] conducted a study in São Paulo and reported an average consumption of 1.19-1.27 kWh/km, of which they found higher energy consumption on hotter days. Different studies provide statistical analyses on energy consumption in relation to temperature [27,28]. Culik et al [27] performed a statistical analysis on 14,888 trips and found that lower temperatures increased energy consumption.…”
Section: Data Analysis In Beb Operationsmentioning
confidence: 99%
“…This means that these items may directly or indirectly collect, process and/or exchange data via a computer network and the Internet. Concurrently, other growing trends on a global scale are the advances in electromobility [2][3][4][5][6][7][8][9], obtaining energy from renewable sources and alternative fuels [10][11][12][13][14][15][16] and reducing exhaust emissions from means of transport [17][18][19][20][21][22][23][24]. The analysis of the literature and the state of knowledge confirmed that there are many technologies on the market for obtaining data from photovoltaic systems, electric car chargers and electricity meters taken from the power grid [2,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of electric vehicles with traction batteries with high energy capacity may be helpful for this purpose. Electric buses with batteries with a capacity of over 200 kWh and passenger vehicles with batteries with a capacity of up to 100 kWh can be charged with DC chargers with adjustable output power [47]. This solution is also helpful for owners of PV systems who have built a system with too much power and are unable to use the energy produced.…”
Section: Introductionmentioning
confidence: 99%